2022
DOI: 10.1111/conl.12912
|View full text |Cite
|
Sign up to set email alerts
|

Fisher–shark interactions: A loss of support for the Maldives shark sanctuary from reef fishers whose livelihoods are affected by shark depredation

Abstract: Targets for protecting predatory species often fail to consider the human costs of conservation. Human-wildlife interactions can increase following conservation action and present a major ecological and socioeconomic challenge. Using semistructured interviews (n = 103), participatory mapping (n = 57) and Baited Remote Underwater Video Stations (50 h) we investigated fisher-shark interactions in one of the world's principal shark sanctuaries. Seventy-three percent of respondents reported an increase in shark de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…In the GoM, anglers have reported rapid and significant increases in shark depredation during the past 5 years (Drymon et al, 2022), and often attribute the interaction to confirmed depredators like sandbar shark and blacktip shark (Drymon et al, 2019). Increasing shark depredation has the potential to negatively impact recreational anglers' perceptions of, and willingness to support, shark conservation (Robinson et al, 2022). Thus, a broader understanding of the degree to which recreational anglers are experiencing depredation will help inform future management and conservation efforts for sharks.…”
Section: Introductionmentioning
confidence: 99%
“…In the GoM, anglers have reported rapid and significant increases in shark depredation during the past 5 years (Drymon et al, 2022), and often attribute the interaction to confirmed depredators like sandbar shark and blacktip shark (Drymon et al, 2019). Increasing shark depredation has the potential to negatively impact recreational anglers' perceptions of, and willingness to support, shark conservation (Robinson et al, 2022). Thus, a broader understanding of the degree to which recreational anglers are experiencing depredation will help inform future management and conservation efforts for sharks.…”
Section: Introductionmentioning
confidence: 99%